PENGEMBANGAN KOMIK SEBAGAI MEDIA BELAJAR MATEMATIKA DI SEKOLAH DASAR - Mochamad Guntur; Siti Sahronih; Zakiyah Ismuwardani (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2023)
The curriculum in Indonesia has been developing from year to year, until now the curriculum applied is the independent curriculum that demands innovation in learning, including the use of teaching materials. In learning mathematics, the teaching materials used were less contextual and minimal in visualization until finally, comics were created as learning media. Characteristic comics can change material that is difficult to reach into material that is easily accessible, this happens because one of the comics is that it can visualize abstract material into something real. The purpose of this research is to make learning media in the form of comics which is further developed because it is based on local wisdom which is expected to be one of the media for learning mathematics for elementary school students. This study uses the Research and Development/ (RD) method, while the model used in this development is the ADDIE (Analysis, Design, Development, Implement, Evaluation) model. The results of this study obtained very good validation with an Aiken value of 0.76 which indicates that the learning media is valid. And, obtaining a practicality test score of 77% which shows that the media is practical and ready to be tested by elementary school students.